Institution-Driven Comparative Advantage and Organizational Choice - Shon Ferguson; Sara Formai (Research Institute of Industrial Economics (IFN), 2012)
The theory of the firm suggests that firms can respond to poor contract enforcement by vertically integrating their production process. The purpose of this paper is to examine whether firms integration opportunities affect the way contract enforcement institutions determine international trade patterns. We find that the benefits of judicial quality for the exports of contract-intense goods are more muted in industries that have a greater propensity towards vertical integration arrangements with input suppliers. We show that our results are not driven by primitive industry characteristics. Our results confirm the role of judicial quality as source of comparative advantage and suggest that this depends not only on the technological characteristics of the goods produced but also on the way firms are able to organize the production process.
Keywords: D23; F10; F14; L22; L23; 330; International Trade; Comparative Advantage; Contract Enforcement; Vertical Integration; Vertikale Konzentration; Finanzmarkt; Institutionelle Infrastruktur; Produktionsorganisation; Komparativer Vorteil; Außenwirtschaftstheorie